Influences on multidisciplinary team decision-making. Issue 2 (1st February 2008) - Lanceley, A.; Savage, J.; Menon, U.; Jacobs, I.
Abstract : The objective is to explore how clinical decisions are made in a cancer multidisciplinary team meeting (MDM). The study design is qualitative based on participant observation, in depth interviews, and questionnaires. The research setting was weekly cancer MDM which provides a forum for clinical debate for practitioners in the field of women's health, working within one Cancer Network in England. The participants were 53 practitioners attending a weekly MDM over a 4-month period. Analysis of nonparticipant observation data and practitioner interview narratives identified key influences on the work of the MDM, and in particular decision-making. The research identified three major influences on the conduct of the MDM. First, MDM discussions are dominated by those with surgical, medical, or diagnostic expertise with limited contributions from those with a nursing, palliative, or psychosocial background. Second, decision-making is shaped by an overriding need to comply with policy initiatives concerning the organization of diagnosis and treatment. The third influence is whether the patient is known or unknown to some degree by members of the MDM. Where there is preexisting knowledge of the patient, the discussion and decision is inclusive of a wider range of disciplines. Team working in these circumstances is an acknowledged source of satisfaction and motivation. Where the patient is not known, discussion concerns only the physical details necessary to make a diagnosis and contributions from the wider team (including those with knowledge of psychosocial care) are rare. Practitioners' sphere of expertise, Department of Health policy, and familiarity of the team with the patient are key factors in shaping decision-making in MDMs.